2014
DOI: 10.1590/0004-282x20140126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspects of patients with sarcoglycanopathies under steroids therapy

Abstract: Patients with sarcoglycanopathies, which comprise four subtypes of autosomal recessive limb-girdle muscular dystrophies, usually present with progressive weakness leading to early loss of ambulation and premature death, and no effective treatment is currently available. Objective: To present clinical aspects and outcomes of six children with sarcoglycanopathies treated with steroids for at least one year. Method: Patient files were retrospectively analyzed for steroid use. Results: Stabilization of muscle stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…On the other hand, providing differential diagnosis to the 17 individuals with other forms of MDs was also useful to determine the suitable standard of care and eligibility on gene-transfer therapies. They were prevented from a corticosteroid treatment, as for these diseases there is still no strong evidence for its efficacy ( Walter et al, 2013 ; Albuquerque et al, 2014 ). Furthermore, six of them could already be determined as candidates for gene-transfer therapies that are under preclinical or clinical tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, providing differential diagnosis to the 17 individuals with other forms of MDs was also useful to determine the suitable standard of care and eligibility on gene-transfer therapies. They were prevented from a corticosteroid treatment, as for these diseases there is still no strong evidence for its efficacy ( Walter et al, 2013 ; Albuquerque et al, 2014 ). Furthermore, six of them could already be determined as candidates for gene-transfer therapies that are under preclinical or clinical tests.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate molecular diagnosis, given by the identification and precise characterization of deleterious variants, is crucial for dystrophinopathy patients to confirm the clinical presumptive diagnosis, to access to the specific and optimal standard of care ( Bushby et al, 2010 ) and determine eligibility for the available pharmacogenetic treatments. For example, molecular confirmation of dystrophinopathy determines applicability of corticosteroid therapy, as DMD is one of the MDs showing fruitful results from this treatment ( Albuquerque et al, 2014 ; Bello et al, 2015 ). On the other hand, molecular diagnosis plays a key role in family planning and, therefore, prevention.…”
Section: Introductionmentioning
confidence: 99%
“…LGMD type 2E/R4 (LGMD2E/R4) is caused by mutations in the β-sarcoglycan gene ( SGCB ), leading to β-sarcoglycan (SGCB) protein deficiency and loss of sarcoglycan complex formation and preventing dystrophin-associated protein complex (DAPC) stabilization 4 , 5 . This loss of protein function manifests clinically in early childhood or late adolescence and progresses to loss of ambulation, potential respiratory insufficiency and often premature mortality 6 8 .…”
Section: Mainmentioning
confidence: 99%
“…Siblings with SGCA-related LGMD received deflazacort for 6 months and showed improved muscle strength and functional assessments [12]. A small retrospective study of 6 patients with LGMD on steroids for at least one year reported conflicting results [13].…”
Section: Introductionmentioning
confidence: 99%